COMPARISON OF TIME FOR MYCOBACTERIUM TUBERCULOSIS GROWTH ON L. J. MEDIUM & BACT/ALERT 3D SYSTEM - ASHISH K. ASTHANA; MOLLY MADAN (International Journal of Pharma and Bio Sciences, 2015)
Main problem for Mycobacterium tuberculosis growth is time. This study evaluates the performance of Bact/Alert 3D system for isolates and identification of mycobacteria. 100 clinical specimens from the chest and tuberculosis department were included. All were positive by Lowenstein Jensen (LJ) media in different time. All samples were also tested by Bact/ALERT 3D system for time management study. Samples were microscopically positive for Ziehl Neelsen staining. 25 negative controls were also studied. Maximum 76% samples showed positivity in 3rd week and Minimum 10% positivity reported in 5th week of incubation in BacT/ALERT 3D system. On the other hand only 31% positivity reported in 3rd week by LJ media. BacT/ALERT 3D system was suitable, less time consuming method over LJ media culture. It may be very useful not only to quick detection but also to provide faster treatment and a better prognosis.